Nanostructured food proteins as efficient systems for the encapsulation of bioactive compounds - Mehdi Mohammadian; Mostafa I. Waly; Maryam Moghadam; Zahra Emam-Djomeh; Maryam Salami; Ali Akbar Moosavi-Movahedi (Food Science and Human Wellness)
Recently, nanoencapsulation was introduced as an efficient and promising approach for the protection, delivery, and site-specific liberation of the nutraceuticals and bioactive ingredients. Food proteins are attractive materials for developing nanocarriers to protect and deliver bioactives due to their unique functional and biological properties. Food proteins extracted from animals and plants have the ability to form different nanostructures including nanoparticles, hollow particles, nanogels, nanofibrillar aggregates, electrospun nanofibers, nanotubular structures, and nanocomplexes. These nanostructured food proteins have been widely used as nanocarriers for the biologically active compounds and drugs. The release of bioactive compounds from nanocarriers depends mainly on pH as well as swelling and the degradation behavior of nanostructure in the simulated physiological conditions. This review presents the applications of the nanostructured food proteins for the encapsulation of bioactive compounds. The major techniques for the fabrication of nanocarriers are described. The encapsulation, protection, and release of bioactive compounds in different nanostructured food proteins were also discussed.